Successful Repair of Iatrogenic Cyclical Menouria - Shamima, Mosammat Nargis; Zereen, Rubayet; Begum, Monwara; Akter, Nurjahan; Khatun, Mst Rowshan Ara; Kowsari, Mosfika (TAJ: Journal of Teachers Association, 2018)
Vesicouterine fistula (VUF) is a very rare occurrence and is estimated to occur in only (1-4%) of all genitourinary fistulas. It is an abnormal pathway between the bladder and the uterus. The most common cause is lower segment caesarean section. Patients usually present in the early post operative period with the problem of continuous urinary incontinence. On the rare occasion, recurrent urinary tract infection, recurrent gross painless haematuria, or secondary infertility associated with secondary amenorrhoea would be the presenting complaint. Among all vesicouterine fistula 90% are Youseef’s Syndrome the least common of the urogynaecological fistulas. Youseef’s syndrome is characterized by cyclic haematuria (menouria), absence of vaginal bleeding (amenorrhea) and urinary incontinence due to vesicouterine fistula (VUF). TAJ 2017; 30(1): 70-72